Green Tea’s Medicinal Benefits in Reducing Methotrexate’s Harmful Effects on the Kidneys - A. Ali, Ali Hassan (Asian Journal of Pharmaceutics (AJP), 2024)
Background: Hundreds of millions of people worldwide consume tea every day because it is a pleasant, wellliked, affordable, socially acceptable, and safe beverage. Drinking green tea is linked to a lower incidence of degenerative diseases and illnesses. Green tea has now been included to other vitamin and nutritional supplements as a dietary supplement. Aims of Study: The purpose of our study was to assess how methotrexate (MTX) administration affected the kidneys and how green tea protected them. Materials and Methods: There were 24 male rats split up into three groups. There were eight rats in each group, and the control untreated group received nothing. The MTX group got one dose (20 mg/kg) MTX intraperitoneally. The last group of rats was given a daily dosage of 36 mg/kg body weight of green tea through a gastric tube for 9 weeks after receiving the same injection of MTX as the second group. At the end of the research, renal functioning and histological alterations were assessed. Results: The second group’s renal architecture was clearly altered, and their serum levels of uric acid, creatinine, and blood urea nitrogen were all elevated. When compared to the MTX group, the kidney’s histological image improved in the green tea and MTX group. Conclusion: All aspects of evidence pointed to oxidative stress as the source of MTX-induced nephrotoxicity, and green tea’s anti-inflammatory and antioxidant properties protect the kidney from this damage. In the group receiving green tea and MTX, the kidneys’ natural structure was largely restored.